An efficient oxic-anoxic process for treating low COD/N tropical wastewater: Startup, optimization and nitrifying community structure. (November 2020) - How, Seow Wah; Nittami, Tadashi; Ngoh, Gek Cheng; Curtis, Thomas P.; Chua, Adeline Seak May
Abstract: In this study, we assessed and optimized a low-dissolved-oxygen oxic-anoxic (low-DO OA) process to achieve a low-cost and sustainable solution for wastewater treatment systems in the developing tropical countries treating low chemical oxygen demand-to-nitrogen ratio (COD/N) wastewater. The low-DO OA process attained complete ammonia removal and the effluent nitrate nitrogen (NO3 –N) was below 0.3 mg/L. The recommended hydraulic retention time and sludge retention time (SRT) were 16 h and 20 days, respectively. The 16S rRNA sequencing data revealed that long SRT (20 days) encouraged the growth of nitrite-oxidizing bacteria (NOB) affiliated with " Candidatus Nitrospira defluvii". Comammox made up 10–20% of the Nitrospira community. NOB and comammox related to Nitrospira were enriched at long SRT (20 days) to achieve good low-DO nitrification performance. The low-DO OA process was efficient and has simpler design than conventional processes, which are keys for sustainable wastewater treatment systems in the developing countries treating low COD/N wastewater. Graphical abstract: Image 1 Highlights: Low-DO OA reactor enhanced N removal in treating low COD/N tropical wastewater. Post-anoxic denitrification phase reduced the effluent NO3 –N to below 0.3 mg/L. The recommended operating HRT and SRT are 16 h and 20 days, respectively. Nitrospira dominated the nitrifying community at long SRT operation (20 days). qPCR revealed potentially novel comammox affiliated with Nitrospira in the reactor.